Implantação e desenvolvimento do Programa de Inovação Educação Conectada na rede municipal de educação de Terra Roxa: desafios e oportunidades - Santos, Simone Francisco dos (2024)
This thesis investigates the implementation of the Connected Education Innovation Program (PIEC) in the public education network of the municipality of Terra Roxa – PR, where, given the reality existing in educational institutions, the question that guided this research was: What are the possible challenges and opportunities arising from the implementation and development of PIEC, considering the initial stage marked by the scarcity of digital devices for use by students and teachers and also by the lack of teaching training related to this topic? The general objective was to construct a feedback related to the possible challenges and opportunities caused by the implementation of the PIEC in the municipal education network of Terra Roxa, considering its context of application and the investigation of lines capable of contributing to the improvement of the Program. As our research is related to issues of social interest, we developed this work through the theoretical perspective of Applied Linguistics, of the Qualitative type. The methodological perspective was through Action Research, enabling a continuous movement to improve the work of the local PIEC coordinator, establishing connections between educational management and teaching practice. The theoretical basis was based on works by scholars such as Gilles Deleuze and Félix Guattari (1995), Hugo Assmann (1998), Michel Serres (2013), Edgar Morin (2008; 2011) and Dal Molin (2003). The methodological proposal was linked to the rhizomatic thinking of Deleuze and Guattari, so that, when following the implementation of PIEC in the municipal network, it was possible to understand the importance of balanced development of four dimensions: vision, training, digital educational resources and infrastructure. We note that this balance really contributes to digital technology being used in a way that promotes the emergence of infinite possibilities for connections and learning experiences.